Repair Design of Packing Tube Operator Work Aids in the Packaging Industry with Nordic Body Map and Anthropometry Methods: Rancangan Perbaikan Alat Bantu Kerja Operator Packing Tube pada Industri Packaging dengan Metode Nordic Body Map dan Antropometri - Novitasari, Melisa; Putra, Boy Isma (Indonesian Journal of Innovation Studies, 2021)
Betts Indonesia a company engaged in manufacturing tube manufacture. This study aims to determine a comfortable working posture to optimize performance and be able to minimize injuries to body parts. Data processing was carried out by measuring body dimensions and distributing research questionnaires to 40 respondents. The method used to see how severe the level of risk of injury is using REBA. Based on the initial calculation process at the packing tube work station using the REBA method, it has an average risk level of 11 which is included in the high risk level and needs to be repaired immediately. After repairing the work aids, the REBA score was 6 which was included in the medium level. The work aids that have been made can help improve the operator's work posture so as to minimize the risk of injury and make it easier to check the product and reduce the level of defects in the product.